Pozitivna diskriminacija u regulaciji i zaštiti prava i sloboda pripadnika nacionalnih manjina - uloga Ustavnog suda Republike Hrvatske - Arlović, Mato (Array, 2019)
Implementing the banning of discrimination is one of the most important tasks of all bodies dealing with the protection of human rights and fundamental freedoms. That is, every achieved outlawing of discrimination is a firm indication of the violation of human rights and fundamental freedoms. However, from that important principle in legal political and overall social relations, there are also exceptions or deviations. They can be seen in the principle of positive discrimination which is a necessary corrective in achieving the rights and freedoms of minorities or underrepresented groups. That is, in democratic societies, where the principle of majority rules, reaching decisions on underrepresented groups, always depends on decisions which the majority reaches. Regardless of how 'democratic' society is, a democratic society with its principle of rule of law cannot allow the majority to freely assess whether it will decide on the legal regulation, achieving and protection of minority rights in order to allow achievement of this in all segments of social relations of important rights and freedoms for their self-actualisation. For this reason, countries with the rule of law, by legally regulating positive discrimination ensure legal constitutional guarantees so that minorities regulate, achieve and protect so called positive rights and freedoms which in turn ensure the self-actualisation of these rights through achieving their ethos. Positive discrimination is precisely therefore one of the most complex, but very sensitive legal, political issues in general. It is necessary. Although positive, it is discrimination, nonetheless. Its sensitivity is present regardless of the fundamentals which it prescribes. However, in relation to some of them, it can have, and most often does have, wider legal, political and even cultural implications. A striking example is the applied principle of positive discrimination among national minorities.